Toxoplasma effector-induced ICAM-1 expression by infected dendritic cells potentiates transmigration across polarised endothelium - Ross, Emily C.; Hoeve, Arne L. ten; Saeij, Jeroen P. J.; Barragan, Antonio (Frontiers in Immunology, 2022)
The obligate intracellular parasite Toxoplasma gondii makes use of infected leukocytes for systemic dissemination. Yet, how infection impacts the processes of leukocyte diapedesis has remained unresolved. Here, we addressed the effects of T. gondii infection on the trans-endothelial migration (TEM) of dendritic cells (DCs) across polarised brain endothelial monolayers. We report that upregulated expression of leukocyte ICAM-1 is a feature of the enhanced TEM of parasitised DCs. The secreted parasite effector GRA15 induced an elevated expression of ICAM-1 in infected DCs that was associated with enhanced cell adhesion and TEM. Consequently, gene silencing of Icam-1 in primary DCs or deletion of parasite GRA15 reduced TEM. Further, the parasite effector TgWIP, which impacts the regulation of host actin dynamics, facilitated TEM across polarised endothelium. The data highlight that the concerted action of the secreted effectors GRA15 and TgWIP modulate the leukocyte-endothelial interactions of TEM in a parasite genotype-related fashion to promote dissemination. In addition to the canonical roles of endothelial ICAM-1, this study identifies a previously unappreciated role for leukocyte ICAM-1 in infection-related TEM.